2017
DOI: 10.1136/bmjresp-2017-000196
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and patient-reported outcomes in subjects with chronic obstructive pulmonary disease: are they independent entities?

Abstract: IntroductionThere is a hypothesis that chronic obstructive pulmonary disease (COPD) is an accelerated ageing disease. Frailty is a geriatric syndrome characterised by physical, psychological and social vulnerability, thought to be a feature of ageing. The authors aimed to explore the relationship between frailty and physiological and patient-reported outcomes (PROs) in subjects with stable COPD.MethodsWe administered the Kihon Checklist that has been validated for frailty screening. We also assessed patient-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 32 publications
(53 reference statements)
2
69
0
Order By: Relevance
“… 8 A recent study reported a prevalence of 21% frailty in patients with COPD using the Kihon Checklist. 11 These studies are lower than a UK population study where the reported prevalence of frailty was 57.8% in 70 COPD patients diagnosed on the basis of symptoms rather an objective measure of airways obstruction. 10 Unlike the latter study, our study population was unselected based on physician defined COPD with mandatory demonstration of airways obstruction at the time of entry to the ARCADE study 15 and hence provided a wider spectrum of disease severity and comorbidities which might account for the variation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 8 A recent study reported a prevalence of 21% frailty in patients with COPD using the Kihon Checklist. 11 These studies are lower than a UK population study where the reported prevalence of frailty was 57.8% in 70 COPD patients diagnosed on the basis of symptoms rather an objective measure of airways obstruction. 10 Unlike the latter study, our study population was unselected based on physician defined COPD with mandatory demonstration of airways obstruction at the time of entry to the ARCADE study 15 and hence provided a wider spectrum of disease severity and comorbidities which might account for the variation.…”
Section: Discussionmentioning
confidence: 72%
“… 8 A recent study reported 21% frailty in a Japanese COPD cohort. 11 In addition to various populations studied, there were differences in study design, methods to assess frailty, and lack of appropriate population controls. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Frailty appeared to have developed via an independent mechanism except for age-related deterioration in patients with COPD. Frailty assessment was recommended to be included as a part of multidimensional measurements of COPD 96. However, similar to FRAIL scale, further validation studies of the KCL in hospitalized COPD patients need to be undertaken.…”
Section: Kihon Checklist (Kcl)mentioning
confidence: 99%
“…1,4 People with both COPD and frailty are at increased risk of mortality 5,6 and readmission within 3-months posthospitalisation for an exacerbation of their disease. 7,8 Compared to people who have COPD but no indication of frailty, they experience poorer physical function and health status, 9 and increased anxiety and depression symptoms. 10 People with COPD and frailty are also less likely to start and complete pulmonary rehabilitation, 10 and have lower levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%